A study of routing and wavelength assignment problems in wavelength routed optical networks - Wang, Ying (2010)
Devising a good routing and wavelength assignment (RWA) scheme is a very important and challenging problem to be addressed in the design of a wavelength routed optical network (WRON). RWA deals with finding a route from a network of physical links for each given pair of source and destination nodes, and appropriately selects and reserves a specific unused wavelength on each of the links along the route. In the context of WRON networks, RWA related problems could be classified into four categories in accordance with the type of traffic pattern and the stage of the design and planning process; they are, namely, static lightpath establishment (SLE) problem, dynamic lightpath establishment (DLE) problem, virtual topology design (VTD) problem, and dynamic label switched path provisioning (DLP) problem.